2014
DOI: 10.5539/ijef.v6n2p62
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Diversification Strategy and the Impacts on the Middle East Real Estate Investment Decision

Abstract: This paper identified and examined the possible impacts of portfolio diversification strategy on the generated Property Companies' (PCs) stocks returns, and the real estate industry performance and risk in the Middle East Real Estate Industry (MEREI) observed over the time period from Feb. 2008to Feb. 2012. It is important to mention that there are two components of portfolio risk; the first one is non-systematic risk which can be diversified. The second one is systematic or non-diversifiable risk, which canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Investors' effort to maximize their returns and minimize their risk will depend on their knowledge and expertise in selecting stocks or indexes. A few studies have examined the strategy of diversified portfolios (Shan Hu et al 2010;Al Bakri, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Investors' effort to maximize their returns and minimize their risk will depend on their knowledge and expertise in selecting stocks or indexes. A few studies have examined the strategy of diversified portfolios (Shan Hu et al 2010;Al Bakri, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, market betas do vary significantly over time; the inter-temporal variation is not nearly large enough to drive average conditional alphas to zero. Al Bakri (2014) identified the impact of portfolio diversification on the generated property company's stock returns and the real estate industry performance and risk in the Middle East. The results showed that there is no distinct relationship between the number of real estate assets held in the portfolio and expected return.…”
Section: An Overview Of Amman Stock Exchangementioning
confidence: 99%